2017
DOI: 10.5123/s1679-49742017000100015
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos geográficos e organizacionais dos serviços de atenção primária à saúde na detecção de casos de tuberculose em Pelotas, Rio Grande do Sul, 2012*

Abstract: organizational and geographic characteristics identified as unsatisfactory may interfere with the detection of tuberculosis cases in Pelotas-RS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…The relationship between patients and health professionals is important for appropriate treatment closure. Studies showed that a high turnover of primary care staff hinders the establishment of these relationships 33,36 . High staff turnover is linked to low salaries and inadequate working conditions 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between patients and health professionals is important for appropriate treatment closure. Studies showed that a high turnover of primary care staff hinders the establishment of these relationships 33,36 . High staff turnover is linked to low salaries and inadequate working conditions 37 .…”
Section: Discussionmentioning
confidence: 99%
“…1 High health professional turnover and delays in health service provision are some of the challenges to improved case notification in the country. 4 In addition, TB is little known by the population, including by health professionals working in primary care. 5 Lack of information about TB is known to be associated with case under-reporting.…”
Section: Increasing Detection and Consequently Case Notification Imentioning
confidence: 99%
“…A quarter of the respondents mentioned having needed to return to the Casais five times, and waiting for more than 30 days to get conclusive diagnosis, similarly to reports from rural areas in India and from interior regions of Brazil. [24][25][26][27] Traditional indigenous medicine appeared among the treatment options, but without excluding biomedicine. Both use of medicinal plants and prayer and/or shamanism, either on their own or in association with use of Western medicine, were considered in treatment.…”
Section: Discussionmentioning
confidence: 99%